Coding in Scratch. - Setford, Steve; Woodcock, Jon. (New York : DK Publishing, 2016)
A fun, practical introduction to coding your own projects in Scratch, the free online coding platform.
-- Hello, Scratch! -- Exploring Scratch -- Weird music -- Skywriting -- Quiz time! -- Pet party -- Bounce painting -- Solutions -- Getting Scratch; note for parents.
Accession number 5962.
Keywords: Scratch (Computer program language) -- Juvenile literature; Computer programming -- Juvenile literature; Microcomputers -- Programming -- Juvenile literature; Programming languages (Electronic computers) -- Juvenile literature; Programming languages (Electronic computers) -- Problems, exercises, etc. -- Juvenile literature